Looking within and beyond the community: Lessons learned by researching, theorising and acting to address urban poverty and health. (January 2014) - Hodgetts, Darrin; Chamberlain, Kerry; Tankel, Yadena; Groot, Shiloh
Urban poverty and health inequalities are inextricably intertwined. By working in partnership with service providers and communities to address urban poverty, we can enhance the wellness of people in need. This article reflects on lessons learned from the Family100 project that explores the everyday lives, frustrations and dilemmas faced by 100 families living in poverty in Auckland. Lessons learned support the need to bring the experiences and lived realities of families to the fore in public deliberations about community and societal responses to urban poverty and health inequality.